The Importance Of Honesty In Marriage In Eugene O'neill's Anna Christie (1921): A Sociological Approach - Sari, Anggraeni Putri; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph.D (2016)
This research is aimed to describe the sociological approach and to describe American society and to analyze Anna Christie drama based on the structural elements of the drama. The data were taken from 89 pages of drama downloaded from http://www.gutenberg.org/ebooks/4025 which were posted in 2009. This research is using descriptive qualitative research and using a sociological approach. The subject of the study is Anna Christie drama written by Eugene O'Neill and has been publicized by The Pennsylvania State University in 2010-2013. It is analyzed by using sociological approach. There are two kinds of data namely primary data and secondary data that are needed to do this research. The techniques of data collection in this research: Reading the script for the several times and repeat, taking note of the important part in primary and secondary data, identifying the topic of the play and analyzing the data based on sociological approach. The data is 89 conversations in English language. This research finds social aspects of Anna Christie drama that honesty is important for individual